Estratégias e táticas do poder com a infância - Serute, Marcelo (2010)
From Foucault is thrown into relief childhood at school / institution: the practices of power, the discursive practices (or discursive formations) - as these theories imply for works of education, which it has been called foucaultian (Veiga- Netto, Ratto, Bujes, Larrosa, Kohan). The source show the experience that circulates the notions of: normativity, subjectivity and the rules of the educational system, but they are inserts with childhood, childhoods of power with and take into account the platform erected for the sociology of childhood and could advance the discussion theoretical, in specific, the image of the invisible children - to the extent that considers sociohistorical and cultural. Thus, the research seeks practical approach to "manage" their childhood, right, practices the power of "domination" of childhood, or is formulated, from that iconic, a problem to be solved in the following investigative situation: About what strategies and tactics of power is exercised control of children in school? Furthermore, behold, one also considers the ethics Foucauldian understanding, this approach has already distended domination. Objective is then to measure these practices through a deal more mobile power, or rather it is a notion of power that circulates and also contrasts the experiences of children in school. Thus, the literature, with qualitative approach, seeks to investigate the discursive practices exercisable on the concept of childhood as it appears woven the threshold of the institution of school, practices that make the child compatible (normal, docile and useful) rules that system. Already on the issue of disciplining diluted interests focus on childhood as a social subject, history, or rather the modern phase (XVII and XVIII) has as main feature the kind of disciplinary society that is, but that legacy is still fluent in educational practices and pedagogical machinery of modern society and school discipline, some, like Deleuze, is the society of control current. The reading of the bibliography of Foucault (and hence the productions that distend) state that work in a critical, interpretative and consistent. For the practical effect - since the last chapter of this work - effective to attempt to propose theories that enhance the resistance (or struggle) of the children often fought precisely from the brink of his own childhood institutionalized by the school.